Accelerator and detector physics at the Bern medical cyclotron and its beam transport line - Auger Martin (Nukleonika, 2016)
The cyclotron laboratory for radioisotope production and multi-disciplinary research at the Bern University Hospital (Inselspital) is based on an 18-MeV proton accelerator, equipped with a specifically conceived 6-m long external beam line, ending in a separate bunker. This facility allows performing daily positron emission tomography (PET) radioisotope production and research activities running in parallel. Some of the latest developments on accelerator and detector physics are reported. They encompass novel detectors for beam monitoring and studies of low current beams.